α2B-ADRENOCEPTORS IN THE REGULATION OF VASCULAR SMOOTH MUSCLE CELL CONTRACTION AND PROLIFERATION - Huhtinen, Anna (fi=Turun yliopisto|en=University of Turku|, 2017)
α2-Adrenoceptors (α2-ARs) belong to the large superfamily of G protein-coupled receptors (GPCRs). They mediate important actions of the endogenous catecholamines adrenaline and noradrenaline. All three α2-AR subtypes are involved in the regulation of blood pressure and vascular tone. α2-ARs can regulate both vascular smooth muscle contraction and remodeling of the blood vessel wall, but the intracellular signaling mechanisms involved in these functions have remained largely unknown. The aim of this thesis was to investigate the involvement of the α2B-AR subtype in the regulation of the contraction and proliferation of vascular smooth muscle cells (VSMC), and to clarify the related cellular signaling mechanisms. In order to characterize the effects of α2B-AR activation on VSMC contraction and proliferation and to investigate whether these functions could be altered by drug treatment, a VSMC line stably expressing the human α2B-AR was generated by transfection of rat A7r5 cells. Characterization of the novel A7r5-α2B cell line indicated that the localization and ligand binding properties of the expressed α2B-ARs were in line with earlier studies of α2B-ARs in different host cell environments, and that the receptors had the expected pharmacological characteristics. Therefore, the generated A7r5-α2B cell line was regarded as a useful tool for investigating the functions and regulation of α2B-ARs in VSMCs. α2B-ARs were demonstrated to be capable of mediating VSMC contraction by using a functional assay measuring myosin light chain phosphorylation, which is a biochemical readout of VSMC contraction. The network of signaling pathways involved in α2B-AR-mediated contraction of A7r5 VSMCs appeared to be complex and seemed to involve many mediators, such as Gi proteins, Gβγ subunits, phospholipase C (PLC), protein kinase C (PKC) and L-type Ca2+ channels. Different screening assays, namely DNA microarray, small inhibitor compound library screening and kinase activity profiling, were used to investigate the genetic regulation and intracellular signaling mechanisms involved in α2BAR-evoked proliferation of A7r5 VSMCs. The cellular mechanisms and signal transduction pathways participating in this response appeared to be complex and included redundancy. The employed screening assays and their respective data analysis approaches were found to be useful as tools to map the activation of cellular signaling networks in a situation where the exact mechanisms still remain unknown. These screening tools were considered suitable for hypothesis generation, but additional approaches will be required for further hypothesis testing.

α2-Adrenergiset reseptorit (α2-AR) ovat G-proteiinikytkentäisiä reseptoreita (GPCR). Ne aktivoituvat adrenaliinin ja noradrenaliinin vaikutuksesta ja välittävät monia tärkei- tä elimistön säätelytehtäviä. Kaikki kolme α2-AR-alatyyppiä osallistuvat verenpaineen säätelyyn. Ne voivat säädellä sekä verisuonen sileän lihaksen (VSL) supistumista että verisuonen seinämän rakenteessa tapahtuvia muutoksia. Näihin toimintoihin liittyvät solusisäiset viestintämekanismit ovat vielä suurelta osin tuntemattomia. Tämän väi- töstutkimuksen tavoitteena oli selvittää α2B-reseptorialatyypin merkitystä VSL-solujen supistumisen ja proliferaation säätelyssä ja näitä vaikutuksia välittäviä solutason vies- tintämekanismeja. Rotan A7r5-solulinjan VSL-soluihin siirrettiin ihmisen α2B-reseptoria koodittava geeni. Tämä tuotti VSL-solumallin, jonka avulla voitiin tutkia α2B-reseptorien vaikutuksia VSL-so- lujen supistumiseen ja proliferaatioon. Kehitetyn A7r5-α2B -solulinjan reseptorien sijainti ja farmakologiset ominaisuudet olivat odotuksia vastaavat. Tämän validoinnin perusteella A7r5-α2B-solulinjan todettiin soveltuvan α2B-reseptorien toiminnan tutkimiseen VSL-so- luissa. Väitöstutkimuksessa osoitettiin, että α2B-reseptorit välittävät VSL-solujen supistus- vasteita. Tätä tutkittiin mittaamalla myosiinin kevytketjujen fosforylaatiota, sillä myosiinin kevytketjujen fosforylaatio on VSL-solujen supistuksen kannalta keskeinen biokemialli- nen tapahtuma. A7r5-soluissa α2B-välitteiseen supistusvasteeseen liittyvät solunsisäiset viestintämekanismit osoittautuivat monimutkaisiksi ja niihin osallistui monia viestinvälit- täjiä, kuten Gi-proteiinit, Gβγ-alayksiköt, fosfolipaasi C, proteiinikinaasi C ja L-tyypin kal- siumkanavat. DNA-mikrosirumäärityksillä, kinaasi/fosfataasi-inhibiittorikirjaston seulon- nalla ja kinaasiaktivaatiota mittaavilla mikrosirumäärityksillä selvitettiin α2B-välitteiseen VSL-solujen proliferaatiovasteeseen liittyvää geenien ilmentymisen säätelyä ja solunsisäi- siä viestintämekanismeja. VSL-solujen proliferaatiovasteen syntyyn liittyvät mekanismit ja viestintäreitit osoittautuivat monimutkaisiksi ja osittain päällekkäisiksi. Käytetyt seulonta- menetelmät ja niihin sovellettavat analyysit todettiin käytännölliseksi lähestymistavaksi tilanteessa, jossa halutaan kartoittaa ennalta tuntemattomia solunsisäisiä viestintämeka- nismeja. Seulontamenetelmät todettiin hyödyllisiksi uusien havaintojen tuottamisessa, mutta havaintojen tuottamien hypoteesien testaamiseen tarvitaan muita, kohdennettuja menetelmiä.